The Use Of Many Listening Media Types In One Hypermedia Listening Environment - Türel, Vehbi (Innovations in Language Teaching Journal, 2024)
The positive effects of using different listening texts (i.e. audio, video) in listening enhancement as a part of FLL are already well known. As hypermedia enables us to combine and present audio and video with other learning elements such as supplementary contextual visuals, animations, and captions more effectively on the same digital platform, audio and video can be presented to language learners in one hypermedia listening application in different forms as different listening media types (i.e. audio-only, audio + supplementary contextual visuals, audio + animation, video-only, talking heads video + supplementary contextual visuals). This study investigated forty-five autonomous intermediate and upper intermediate NNSs learners' perceptions of the use and priority of different listening media types in one hypermedia that aimed to enhance the listening skills of the participants. The results revealed that the learners are in favour of the presence of different listening media types in one hypermedia. The learners believe that the presence of different listening media types in one hypermedia listening environment (HLE) improves their listening skills and helps prepare them for the real-world. Similarly, learners prefer some listening media types more than others in one HLE. In the same way, not only do learners think that some listening media types improve their listening more than others, but learners also believe that some listening media types prepare them better for the real-world.